2012
DOI: 10.1007/s00221-012-3292-4
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in finger force control are characterized by reduced force production

Abstract: It has been repeatedly shown that precise finger force control declines with age. The tasks and evaluation parameters used to reveal age-related differences vary between studies. In order to examine effects of task characteristics, young adults (18-25 years) and late middle-aged adults (55-65 years) performed precision grip tasks with varying speed and force requirements. Different outcome variables were used to evaluate age-related differences. Age-related differences were confirmed for performance accuracy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
42
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 37 publications
5
42
0
2
Order By: Relevance
“…Found that the force tracking accuracy (TWR) at ApEn (complexity level) = 0.06 was lower by 19% than that at ApEn = 0.03 and the force tracking variability (RRMSE) higher by 30%. The aforementioned result corresponds to Vieluf et al (2013) which found 30% reduction of force control capabilities in the sinusoidal wave composed of high-frequency by five times.…”
Section: Discussionmentioning
confidence: 61%
“…Found that the force tracking accuracy (TWR) at ApEn (complexity level) = 0.06 was lower by 19% than that at ApEn = 0.03 and the force tracking variability (RRMSE) higher by 30%. The aforementioned result corresponds to Vieluf et al (2013) which found 30% reduction of force control capabilities in the sinusoidal wave composed of high-frequency by five times.…”
Section: Discussionmentioning
confidence: 61%
“…It has been repeatedly shown that movements of the upper extremities of older adults are slower and less precise than those of younger subjects (Cole 1991;Voelcker-Rehage and Alberts 2005;Vieluf et al 2013). It is also known that older adults produce grip forces that are about two times higher than those of younger adults if it is required to grasp and hold objects of different weights and surface textures (Cole 1991).…”
Section: Age-related Differences In Manual Dexteritymentioning
confidence: 99%
“…운동지속불능증(motor impersistence)은 동작의 지속에 문제가 있는 장애로서 <Figure 2>(b)와 같이 20초간 눈 감은 상태를 유지하는 작업으로 평가된다 (Sander, 2010). 운동보속증(motor preservation)은 자극이 사라져도 현재 상태를 유지해 동작의 종결이 지연되는 장애로서 <Figure 2>(c)와 같이 Luria loop를 그리게 한 후 동작을 중지시키는 작 업으로 평가된다 (Chin et al, 2012;Luria, 1965 과 같이 다양하게 제시되는 목표힘 수준을 최대한 정확하게 추적하게 함으로써 평가되고 있다 (Lindberg et al, 2012;Nagasawa et al, 2013;Vieluf et al, 2013;Voelcker-Rehage and Alberts, 2005 (Pincus et al, 1991). 마지막으로, 파형은 기 존 문헌들 (Nagasawa et al, 2013;Lindberg et al, 2012;Naik et al, 2011;Lodha et al, 2010;Voelcker-Rehage and Alberts, 2005) 의 중앙값인 30초로 구성되었으며, 최초 5초간은 기준힘까지 직선으로 도달하도록 구성되었다.…”
unclassified
“…마지막으로, 파형은 기 존 문헌들 (Nagasawa et al, 2013;Lindberg et al, 2012;Naik et al, 2011;Lodha et al, 2010;Voelcker-Rehage and Alberts, 2005) 의 중앙값인 30초로 구성되었으며, 최초 5초간은 기준힘까지 직선으로 도달하도록 구성되었다. (Vieluf et al, 2013). 한편, 최초 5초까지의 힘 추적 data는 분석에서 제외되었다.…”
unclassified
See 1 more Smart Citation